Crossmodal Constraints on Human Perceptual Awareness: Auditory Semantic Modulation of Binocular Rivalry - Chen, Yi-Chuan; Yeh, Su-Ling; Spence, Charles (Frontiers in Psychology, 2011)
We report a series of experiments utilizing the binocular rivalry paradigm designed to investigate whether auditory semantic context modulates visual awareness. Binocular rivalry refers to the phenomenon whereby when two different figures are presented to each eye, observers perceive each figure as being dominant in alternation over time. The results demonstrate that participants report a particular percept as being dominant for less of the time when listening to an auditory soundtrack that happens to be semantically congruent with the other alternative (i.e., the competing) percept, as compared to when listening to an auditory soundtrack that is irrelevant to both visual figures (Experiment 1A). When a visually-presented word was provided as a semantic cue, no such semantic modulatory effect was observed (Experiment 1B). We also demonstrate that the crossmodal semantic modulation of binocular rivalry was robustly observed irrespective of participants’ attentional control over the dichoptic figures and the relative luminance contrast between the figures (Experiments 2A and 2B). The pattern of crossmodal semantic effects reported here cannot simply be attributed to the meaning of the soundtrack guiding participants’ attention or biasing their behavioral responses. Hence, these results support the claim that crossmodal perceptual information can serve as a constraint on human visual awareness in terms of their semantic congruency.